Grounding Line Strain Grid Surveys, Kamb Ice Stream, Antarctica - Hulbe, Christina (IEDA: US Antarctic Program Data Center, 2011)
Abstract: This data set provides the results from a strain grid survey deployed across the Kamb Ice Stream grounding line on the West Antarctic Ice Sheet. The grid was deployed in 2006 and resurveyed in 2007 using a Global Positioning System (GPS). Parameters measured include latitude, longitude, and height of each survey mark in the strain grid, as well as northing, easting, elevations, and displacement of each point during the year between surveys. Data are available via FTP in Microsoft Excel (.xls) format.